Comments on editorial in American Medical Association Journal, 25 September 1948 - Journal of the American Medical Association (1948)
1948 1948 1940s 2 pages - 2 - The Journal goes on to paint a recklessly exaggerated picture of delays in obtaining treatment and doctors' difficulties in dealing with the volume of their patients. The population of England and Wales prior to the introduction of the Service was just over forty-two millions, and the number of available general practitioners was approximately twenty-thousand. As the introduction of the new Service has not altered these figures, if there has been an increase in the numbers being treated by doctors, the explanation must be that under the new Service adequate medical treatment has now for the first time become available to people who did not get it before. The facts are that prior to the new Service, over twenty million people were already entitled to general practitioner treatment as "insured persons" under the old National Health Insurance legislation. No similar provision was made for the families of insured persons. It was the avowed object of meeting this generally recognised difficulty that the new Service made general practitioner treatment available to everyone. We in this country are determined that so long as shortages prevail, whether of medical facilities, food or other essentials, available resources shall as far as possible be shared equally. We are convinced that the health of the community can best be assured not by the abandonment of this principle but by active measures to overcome existing shortages and by maximum efficiency in the use of what is available. The shortages of doctors, hospitals and nurses referred to by the Journal exist and will have to be made good. At the same time, we believe that the skill and efficiency of our doctors and other health workers are not below the standard of any other country. Indeed, we are justifiably proud of the advances of British medicine in many fields. The object of the National Health Service is to make that skill available on a wider basis to the whole community. In conclusion, so far from it being generally true that the doctors are "satisfied that they cannot work the Act", it has been placed on record on behalf of the great bulk of the profession that they are sincerely determined to play their part in building up a first-class service. As to the public, their support of the Scheme and their confidence in its success cannot be questioned. The latest figures show that no less than ninety-two per cent. of the population are now on doctors' lists; the total is increasing daily and there is every reason to believe that by the end of the year practically everyone will be participating in the Scheme. 292/847/5/102